2015
DOI: 10.1186/s13287-015-0093-2
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stromal cell therapy attenuated lung and kidney injury but not brain damage in experimental cerebral malaria

Abstract: IntroductionMalaria is the most relevant parasitic disease worldwide, and still accounts for 1 million deaths each year. Since current antimalarial drugs are unable to prevent death in severe cases, new therapeutic strategies have been developed. Mesenchymal stromal cells (MSC) confer host resistance against malaria; however, thus far, no study has evaluated the therapeutic effects of MSC therapy on brain and distal organ damage in experimental cerebral malaria.MethodsForty C57BL/6 mice were injected intraperi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 47 publications
1
27
0
Order By: Relevance
“…Experimental M‐ALI is characterized by cytokine production, alveolar collapse, neutrophil accumulation in the lung parenchyma, and the impairment of lung mechanics . Indeed, modulation of the lung inflammatory response has been shown to attenuate M‐ALI . LXA 4 has been demonstrated to attenuate the inflammatory response in experimental models of LPS‐induced ALI by preventing neutrophil accumulation and restoring endothelial barrier integrity .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental M‐ALI is characterized by cytokine production, alveolar collapse, neutrophil accumulation in the lung parenchyma, and the impairment of lung mechanics . Indeed, modulation of the lung inflammatory response has been shown to attenuate M‐ALI . LXA 4 has been demonstrated to attenuate the inflammatory response in experimental models of LPS‐induced ALI by preventing neutrophil accumulation and restoring endothelial barrier integrity .…”
Section: Discussionmentioning
confidence: 99%
“…The following changes have also been observed in M‐ALI models: pulmonary dysfunction early after malaria induction, cytokine production, and the presence of parasitized erythrocytes and inflammatory cells in the lung parenchyma . In this context, the modulation of neutrophil accumulation in lung tissue has been hypothesized to have a beneficial impact on host outcome …”
Section: Introductionmentioning
confidence: 99%
“…Souza and colleagues [ 1 ] evaluate, for the first time, the effects of BM-MSC therapy in multiple organ dysfunction during experimental cerebral malaria, and demonstrate that administration of BM-MSCs results in reduced mortality and parasitemia. Although plenty of challenges lie ahead, the results of this study validate the promise of BM-MSC therapy in the treatment of cerebral malaria.…”
Section: Discussionmentioning
confidence: 99%
“…Even patients that are given standard antimalarial therapy at an early phase still face a high risk of dying despite clearance of the parasite, while approximately 25 % of survivors may develop neurological complications and cognitive impairment. In a recent issue of Stem Cell Research & Therapy , Souza and colleagues [ 1 ] observed that administration of bone marrow-derived mesenchymal stromal cells (BM-MSCs) increased survival and reduced parasitemia and malaria pigment deposition in the spleen, liver, kidney and lung in an experimental mouse model of cerebral malaria. Their findings may provide a new option for the treatment of cerebral malaria.…”
mentioning
confidence: 99%
“…Several approaches aiming the inflammatory response have been studied in patients diagnosed with uncomplicated malaria [114,115]; however, the treatment of severe malaria includes only supportive treatment. On the other hand, the use of experimental models of severe malaria suggested that the induction of cytoprotective pathways in brain as well the administration of anti-inflammatory drugs improve the survival of P. berghei-infected mice, especially when administrated as adjunctive treatment to antimalarial drugs [71,76,116,117]. Indeed, a robust clinical evidence is yet necessary to provide the effectiveness of the treatment with inflammatory modulators as an adjunctive therapy to antimalarial drugs to improve patient outcomes.…”
Section: Discussionmentioning
confidence: 99%